The impact of reciprocating and rotary instrumentation on postoperative pain - GENÇOĞLU, NİMET (My University, 2019)
The Impact of Reciprocating and Rotary Instrumentation on Postoperative Pain Nimet Gencoglu1 , Anil Ozgun Karatekin1 , Mustafa Gundogar2 1Endodontics, Marmara University,Faculty of Dentistry, Turkey, Turkey, 2Endodontics, Medipol University, Istanbul, Turkey Objectives The aim of this study was to assess postoperative pain in prospective randomized clinical trial comparing two groups using Reciproc Blue or Hyflex EDM in one visit of endodontic treatment. Methods The study included 30 patients aged (18 and over) with asymptomatic pulp necrosis in mandibular molar and premolar teeth. Patients were randomly assigned to two groups according to instrumentation system.The single session endodontic treatment was performed by one endodontist. Mechanical preparation of the root canals was performed using Reciproc Blue or HyFlex EDM systems. Postoperative pain was recorded using verbal rating scale (VRS) with numbers related to pain levels as follows:0(no pain), 1(mild pain), 2(moderate pain), 3(severe pain) and verbal description with well-defined categories at four following time intervals: 24 h, 48 h, 72 h and 7 days after endodontic treatment. Data were analyzed by Khi-square test. Results The patient in Hyflex EDM reported significantly lower postoperative pain levels at 48h and 72 h than Reciproc Blue group (p<0.0005).The incidence of postoperative pain was found 47% in 24h, 14% in 48h , 14 % in 72h and 0% in 7 days in Reciproc Blue group. However, post operative pain rate was found to be 40% after 24h and no pain in 48h, 72h or 7 days in 17 Hyflex EDM group. None of the patients presented severe pain at the time intervals assessed. Conclusions Reciproc Blue system showed to more incidence of postoperative pain than Hyflex EDM in 24 h and 72 hours intervals
Keywords: Diş Hekimliği; Klinik Bilimler; Endodonti; Sağlık Bilimleri; Dentistry; Clinical Sciences; Endodontics; Health Sciences; Klinik Tıp (MED); Klinik Tıp; DİŞ HEKİMLİĞİ, ORAL CERRAHİ VE TIP; Clinical Medicine (MED); CLINICAL MEDICINE; DENTISTRY, ORAL SURGERY & MEDICINE; Periodontoloji; Ortodonti; Ağız Cerrahisi; Diş Hijyeni; Dişçilik Hizmetleri; Diş Hekimliği (çeşitli); Periodontics; Orthodontics; Oral Surgery; Dental Hygiene; Dental Assisting; Dentistry (miscellaneous); General Dentistry